Upaya Peningkatan Hasil Belajar Siswa melalui Sharing dan Media Audio Visual pada Materi Toleransi sebagai Alat Pemersatu Bangsa Kelas XI BKP SMK Negeri 2 Karang Baru - Jasmaniah (Medan Resource Center, 2022)
This study aims to determine the improvement of student learning outcomes by applying audio-visual media to tolerance material as a unifying tool for the nation's subjects of Islamic Religious Education and Budi Pekerti. The research used is research that uses Classroom Action Research (CAR) or classroom action research with the type of participant CAR research and discovery learning approach. This research is more about solving a problem whose results are described thoroughly. The research subjects in this CAR are students of class XI SMK Negeri 2 Karang Baru, Aceh Tamiang Regency. The results of this study indicate that student learning outcomes, especially tolerance material as a unifying tool for the nation in the subjects of Islamic Religious Education and Character Education during the application of audio-visual media have increased, as seen from the average value before implementation is 73.3, after using the media. audio-visual, the learning outcomes in the first cycle increased with an average value of 77.21 and in the second cycle it reached 86.41. So, the use of audio-visual media can improve the learning outcomes of class XI students in the subjects of Islamic Religious Education and Character Education, especially tolerance material as a unifying tool for the nation at SMK Negeri 2 Karang Baru, Aceh Tamiang Regency.